Biological features of various streptomyces strains as potential agents of phytopathogens biocontrol - A. V. Bakulina; E. V. Tovstik; E. A. Bessolitsyna; N. V. Novoselova; N. S. Zhemchuzhina (Аграрная наука Евро-Северо-Востока)
The article presents the results of studying the biological characteristics (antagonistic and cellulase activity, antibiotic resistance, indolyl-3-acetic acid (IAC) production, the presence of polyketide synthase and cellulase genes) of 13 bacterial strains of the genus Streptomyces. The screening revealed a strain of Streptomyces sp. 2K10 with a high level of antifungal activity against the pathogen Fusarium petroliferatum; three strains (RPLN23, 1N8, 3N2) – antagonist of the causative agent of wheat septoria nodorum blotch (Parastagonospora nodorum). As a biocontrol agent of phytopathogens, the most promising strain among the studied streptomycetes is RPLN23, characterized by antifungal activity (diameter of inhibition zones 24–30 mm), the presence of PKS II genes (229 bp) and the ability to synthesize IAA. For biocontrol of bacterial and fungal pathogens, it is proposed to use the strain Streptomyces sp. 3N3. The work also revealed strains capable of effective destruction of carboxymethylcellulose (RPLN12, 2K9 and 3K9), and strains with genes encoding cellulases of the GH74 family (RSFN5, RPLN12, 3N2) in the genome. A number of streptomyces (RSFN5, RPLN5), which did not show antagonism to the studied cultures of fungi and bacteria, are at the same time interesting for the presence of the PKS II and GH74 genes. Most of the streptomyces studied in the work are sensitive to antibiotics of various groups: aminoglycosides, tetracycline, polypetides, chloramphenicols ansamycins and macrolides, but not β-lactams. The obtained data contribute to the disclosure of the potential of streptomyces for their practical use.